Brittle stars from the British Oxford Clay: unexpected ophiuroid diversity on Jurassic sublittoral mud bottoms. (3rd April 2017) - Ewin, Timothy A.M.; Thuy, Ben
Abstract: Three new ophiuran species, Enakomusium whymanae n. sp., Aspidophiura ? seren n. sp., and Ophiotitanos smithi n. sp., and an unnamed specimen assignable to the genus Dermocoma are described from the Callovian to Oxfordian Oxford Clay Formation of Great Britain. These determinations are based on new finds and a critical reassessment of historic specimens. The Oxford Clay ophiuroids represent two loose assemblages, one from the middle Callovian Peterborough Member and the other from the lower Oxfordian Weymouth Member. Both assemblages accord well with coeval midshelf mud bottom ophiuroid communities in terms of taxonomic composition and relative abundance of taxa. The British Oxford Clay ophiuroids are particularly significant as they are one of the rare instances where multiple species are represented, almost exclusively, by exceptionally preserved articulated skeletons. This provides an important window into the understanding of mid-Upper Jurassic ophiuroid paleobiology.